PARENT AND STUDENT RESPONSE TO THE TEACHER'S LEARNING PROCESS USING LEARNING VIDEO THROUGH YOUTUBE IN SD MUHAMMADIYAH CIPETE - Verellya Caesa Paksi; Sri Harmianto (PROGRES PENDIDIKAN, 2022)
The covid-19 pandemic situation requires all fields of education to change learning by utilizing technology during the Distance Learning period Online learning is the government's solution to require students to do learning at home through parental guidance with teacher supervision. Parents have a special task in implementing this online learning. The existence of this online learning condition, education in Indonesia must be able to make good use of technology for the learning process, one of which is by utilizing learning videos through Youtube. Youtube is a very popular website today that can be used in the world of education. Youtube provides information on the development of science in various fields of education and also has interactive facilities for discussion. From the use of learning videos through Youtube in several elementary schools, one of those who have utilized learning videos through Youtube is SD Muhammadiyah Cipete, so that learning videos through Youtube get various responses from parents and students regarding the effectiveness of learning using Youtube and the obstacles experienced by parents and students when carrying out learning through Youtube, including signal constraints and lack of parental time in accompanying children to study at home.